﻿A fantastic new species of secretive forest frog discovered from forest fragments near Andasibe, Madagascar - Carl R. Hutter (Pensoft Publishers, 2021)
We describe a fantastic new species of forest frog (Mantellidae: Gephyromantis: subgenus: Laurentomantis) from moderately high elevations in the vicinity of Andasibe, Madagascar. This region has been surveyed extensively and has a remarkably high anuran diversity with many undocumented species still being discovered. Surprisingly, by exploring areas around Andasibe that lacked biodiversity surveys, we discovered a spectacular and clearly morphologically distinct species, previously unknown to science, Gephyromantis marokoroko sp. nov., documented for the first time in 2015. The new species is well characterised by a very rugose and granular dorsum, dark brown skin with bright red mottling, sparse light orange to white spots on the ventre, vibrant red eyes and femoral glands present only in males that consist of eight medium-sized granules. Bioacoustically, the new species has a quiet advertisement call that differs from related species by having a moderate call duration, 2–4 strongly pulsed notes and a slow note repetition rate. Furthermore, it has substantial differentiation in mitochondrial DNA, with pairwise distances of 7–9% to all other related species in sequences of the mitochondrial 16S rRNA marker. Additional evidence is given through a combined four mitochondrial markers and four nuclear exons concatenated species tree, strongly supporting G. striatus as the sister species of the new species in both analyses. The discovery of this new species highlights the need for continued inventory work in high elevation rainforests of Madagascar, even in relatively well-studied regions.